Measuring immigration policies: the IMPIC database - Marc Helbling; Liv Bjerre; Friederike Römer; Malisa Zobel (European Political Science, 2017)
Despite a growing interest in migration questions, it is still not possible to systematically analyse immigration policies across time and a large number of countries. Most studies in this field have heretofore focussed on individual cases. Recently, there have been a series of studies that have proposed policy indices that allow for large-N analyses. It appears, however, that these studies have not always adequately addressed the main challenges of index building, that is, conceptualisation, measurement and aggregation. Moreover, they are for the most part limited to individual policy fields or there is a trade-off between the number of countries and years that are covered. The aim of this article is to present the Immigration Policies in Comparison (IMPIC) project, which proposes a new and comprehensive way to measure immigration regulations. The data set covers all major fields and dimensions of immigration policies for thirty-three OECD countries between 1980 and 2010. This article discusses the way immigration policies have been conceptualised, how policies have been measured and aggregated and demonstrates the potential of such a new data set.
Keywords: 300; immigration; policy; measurement; aggregation